1973
DOI: 10.1508/cytologia.38.311
|View full text |Cite
|
Sign up to set email alerts
|

Cytological Studies of Desynaptic Stock in Pearl Millet, <i>Pennisetum typhoides</i> (Burm.) S. and H

Abstract: Desynapsis is defined as a condition in which chromosomes pair initially but as the meiotic division progresses, the chromosomes start falling apart. At diakinesis one can see all or most of these lying as unpaired chromosomes. The occurrence of unpaired chromosomes (univalents) is due to the failure of chiasma formation and is considered to be under the control of recessive genes when present in homozygous condition (Riley and Law 1965). Spontaneous or directed mutation of a single gene leads to unpairing of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

1975
1975
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Univalents are often found to be randomly distributed at metaphase I (John & Lewis, 1965;Singh et al, 1977;Dhesi et al, 1973). During the present investigation it was observed that the orientation of univalents was either polar or they 69 remained in the equatorial region, depending on the number of bivalents present in the cell.…”
Section: Discussionmentioning
confidence: 52%
“…Univalents are often found to be randomly distributed at metaphase I (John & Lewis, 1965;Singh et al, 1977;Dhesi et al, 1973). During the present investigation it was observed that the orientation of univalents was either polar or they 69 remained in the equatorial region, depending on the number of bivalents present in the cell.…”
Section: Discussionmentioning
confidence: 52%
“…S1 and Table 2). John and Lewis [13] demonstrated the random distribution of univalents at MI, which was confirmed by Dhesi et al [5] in pearl millet and by Singh et al [37] in mung bean and in Anogeissus sericea var. sericea by Rao and Kumar [34], and recently Sharma et al [35] in Panax sikkimensis.…”
Section: Discussionmentioning
confidence: 54%
“…These observation draw support from various investigations on Schistocera gregaria [12], Crotalaria juncea [45] and in Phlox drummondii [33], thus confirm the deviant synaptic behavior of M. spathulata. Barring a few reports [5,6,34,35] the natural occurrence of synaptic mutants, particularly in natural populations of higher plants, is a rare phenomenon with little morphological variation to differentiate between the mutant and the normal individual [35]. Synaptic mutations have been reported in natural populations of perennial rhizomatous herbs i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Tradescantia (Celarier 1955), Datura (Bergner et al 1934), Nicotiana (Clausen 1931), Triticum (Li et al (1945), Hordeum vulgare (Enns andLarter 1960, Sharma andReinbergs 1974), Allium cepa (Koul 1962, Kaul 1975, A. amplectens (Levan 1940), Pennisetum typhoides (Dhesi et al 1973, Singh et al 1977, P. ramosum (Jauhar et al 1971), Godetia (HA kensson 1943, Coleus (Vasudevan et al 1967), Rye grass (Ahloowalia 1969a, b), Solanum vendlandii (Cheenaveeraiah and Krishnappa 1968), Colocasia antiquorum (Krishnan et al 1970), Amorphophallus companulatus (Magoon and Sadasivaiah 1967), Sorghum (Sadasivaiah and Magoon 1965), Avena (Thomas and Rajhathy 1966), Pisum sativum (Gottschalk 1978). Contrary to the long list of desynaptic plants, asynapsis has been reported in only few viz.…”
mentioning
confidence: 99%